2011
DOI: 10.1371/journal.pone.0021193
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Photoreceptor Degeneration by Curcumin in Transgenic Rats with P23H Rhodopsin Mutation

Abstract: The P23H mutation in the rhodopsin gene causes rhodopsin misfolding, altered trafficking and formation of insoluble aggregates leading to photoreceptor degeneration and autosomal dominant retinitis pigmentosa (RP). There are no effective therapies to treat this condition. Compounds that enhance dissociation of protein aggregates may be of value in developing new treatments for such diseases. Anti-protein aggregating activity of curcumin has been reported earlier. In this study we present that treatment of COS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 65 publications
2
57
0
2
Order By: Relevance
“…Frederick et al (60) then generated a P23H TG mouse on a rhodopsin knock-out background, and they reported that GHL (P23H)/ Rho Ϫ/Ϫ mice failed to form ROS and that P23H rhodopsin mainly accumulated in the outer nuclear layer. P23H TG rat line-3 is the most commonly used animal model for gene therapy and drug testing (12,21,22,(77)(78)(79)(80)(81)(82)(83), but immunochemistry showed rhodopsin is localized in the ROS of this TG rat (84). The P23H transgene has also been expressed in Xenopus, revealing an inner segment accumulation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Frederick et al (60) then generated a P23H TG mouse on a rhodopsin knock-out background, and they reported that GHL (P23H)/ Rho Ϫ/Ϫ mice failed to form ROS and that P23H rhodopsin mainly accumulated in the outer nuclear layer. P23H TG rat line-3 is the most commonly used animal model for gene therapy and drug testing (12,21,22,(77)(78)(79)(80)(81)(82)(83), but immunochemistry showed rhodopsin is localized in the ROS of this TG rat (84). The P23H transgene has also been expressed in Xenopus, revealing an inner segment accumulation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations leading to the altered conformation of proteins have been shown to be the underlying cause of several dominant neurodegenerative diseases, including dominant retinitis degenerations. Protein misfolding leading to altered trafficking and aggregation are common features of these conditions (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In the Tg P23H rat, where the onset of photoreceptor degeneration is significantly later compared with the Tg pig. 28,30 In addition to curcumin 17 other compounds that produce positive results include: safranal, 36 cannabinoid agonist HU210, 37 tauroursodeoxycholic acid (TUD-CA) 38 proinsulin, 39 Tat-lCL (specific peptide inhibitor of mitochondrial l-calpain), 40 and arimoclomol (heat-shock response coinducer). 41 Neither our study nor the work in the rat have explored the long-term effects of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…17 This is the same mutation that underlies the most common form of autosomal dominant RP in North America. 18 Curcumin, administered from P30 to P70, inhibited severe retinal rod PR degeneration in transgenic P23H rats, which was correlated with dissociated mutant protein aggregation and translocation of mutant rhodopsin to the appropriate cellular compartment.…”
Section: Introductionmentioning
confidence: 99%